Investigation of CBR Value of Sylhet Sand Blended With Local Sand - Asma Ul Hosna; Abu Saleh Sagor (Emerging Technologies and Engineering Journal)
This study investigates the California Bearing Ratio (CBR) values of laboratory-compacted mixtures of Sylhet sand blended with local Rupsha sand to optimize pavement subgrade strength. The physical properties, optimum moisture content, maximum dry density, and CBR values were determined for various mix proportions. A linear relationship was identified between Sylhet sand content and maximum dry density, indicating a decrease in dry density with the inclusion of Rupsha sand. Similarly, the CBR value decreased linearly as more local sand was added. The equations derived from these relationships provide a standardized approach for engineers to determine optimal mix proportions for achieving targeted CBR values, ensuring adequate load-bearing capacity for pavement subgrades. These findings are valuable in pavement design, helping determine the necessary thickness of pavement layers to enhance road durability. Furthermore, this study highlights the importance of site-specific trial mixes to assess the impact of incorporating local sand on the strength and stability of pavement materials.